Opodatkowanie działalności rolniczej podatkiem od towarów i usług: [Taxation of agricutur activity value added tax] (Studia Prawnicze / The Legal Studies, 2007)
Stosownie do postanowień art. 93 i 94 Traktatu Rzymskiego pełnej harmonizacji podlegają przepisy państw członkowskich UE normujące podatki pośrednie w zakresie niezbędnym do swobodnego i niepoddanego kontroli granicznej przepływu towarów i usług.W sferze obrotu produktami rolnymi zasadnicze znaczenie ma harmonizacja przepisów podatku od towarów i usług. Proces dostosowania zapoczątkowała I dyrektywa Rady 67/227/EEC z dnia 11 kwietnia 1967 r. w sprawie harmonizacji przepisów państw członkowskich w zakresie podatków pośrednich. Postanowienia I dyrektywy uznawane są za podstawę funkcjonowania wspólnego europejskiego systemu podatku od wartości dodanej - VAT, przez który ro zumie się powszechny podatek obciążający konsumpcję, stosowany do towarów i usług proporcjonalnie do ich ceny, niezależnie od liczby transakcji, które mają miejsce w procesie produkcji i dystrybucji. Postanowienia powołanej dyrektywy zobowiązywały wszystkie państwa do zastąpienia w terminie do 1 stycznia 1972 r. dotychczasowych krajowych regulacji podatków obrotowych wspólnym systemem podatku od wartości dodanej. W kolejnych latach wydane zostały dalsze dyrektywy konstruujące wspólne dla państw członkowskich opodatkowanie pośrednie.Dla obowiązującego wspólnotowego systemu opodatkowania podatkiem VATzasadnicze znaczenie ma VI dyrektywa Rady 77/388/EEC z dnia 17 maja 1977 r. w sprawie harmonizacji przepisów państw członkowskich dotyczących podatków obrotowych - wspólny system podatku od wartości dodanej: ujednolicona podstawa wymiaru podatku. Określiła ona podstawowe założenia dla wspólnego systemu podatkowego, a przede wszystkim: podatników, podstawę i przedmiot opodatkowania, stawki i zwolnienia, a także zasady i warunki stosowania specjalnych zasad opodatkowania.  In accordance with the provisions of Art. 93 and 94 of the Romę Treaty, the regulations of the EU Member States on indirect taxes are fully harmonized, as far as it is necessary for free trading of goods and services without frontier control limitations. The harmonization of value added tax regulations is of fundamental significance in the tumover of agricultural products. The most important regulation for valid Community VAT taxation system is the Sixth Council Directive 77 / 388 / EEC of 17-th May 1977 on the harmonization of the laws of Member States relating to turnover taxes - Common system of value added tax: uniform basis of assessment. The agricultural production was included in the Community value added tax system. A special simplified system of VAT assessment and collection for agricultural producers was formed, complementary to the generał system.  The simplified Community VAT taxation system of agricultural production is construed on two basie assumptions. Firstly- the reduction of excessive complications resulting from generał principles of taxation; secondly-partial tax refund for lump-sum agricultural taxpayers of value added tax paid for the purchase of means necessary for agricultural production.The concept of VAT taxation of agricultural activities in Polish law has evolved, a evidenced in successive statutory norms of indirect taxes. The harmonization of Polish and Community regulations, relating to the taxation of agricultural producers, was finally effected in the VAT law of 11-th March 2004. Delivery of agricultural products and agricultural services are considered as subject to value added tax, as stipulated in the Sixth Council Directive. The taxation rules are however varied. Farmers subject to special producers are named lump-sum taxpayers; other farmers are taxed according to generał rules. The taxation method, on the day when the VAT regulations is agriculture came in force, was so constructed that almost all existing agricultural producers became ex lege lump-sum taxpayers.The VAT law proved elear inconsistencies in the definition of such elementary terms as agricultural activity, agricultural household and lump-sum farmer. The object of taxation is also not defined in conformity with the reąuirements of levy law.As shown above, there is no fixed normative concept of treating agricultural producers as entrepreneurs, neither are their production and the production effects considered as business activity. Conseąuently, no fixed normative concept of VAT taxation has been developed.